Prawne i finansowe aspekty transakcji giełdowych (na przykładzie giełd towarowych) - Drewiński, Marek (Legal and Financial Aspects of Market Transactions Exemplified by Commodities Markets, 2007)
The article is an attempt of introducing of some chosen legal and financial aspects of functioning of American and European markets. Typical kinds of misappropriation and offences in market turnover and their consequences for investors and brokerage offices have been discussed. The second part of the paper presents standard procedures of market operations' financial control which are legally binding on the US markets. The knowledge of these procedures is of essential practical importance because of the organizational and training co-operation of CME and the Warsaw commodities market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 124-132